Into the wonders of surfactant behaviour - Suhaimi, Hamdan (2000)
In the area of physical chemistry, a topic, which all chemistry undergraduates must encounter, is chemical equilibrium. One very important aspect in this topic and is perhaps surprising, considering its great importance, that little or no attention is given in undergraduate courses is to teaching students the equilibrium between different phases. Even more irony is that the preparation of most commonly used chemical products needs the understanding of phase behavior as an intensified research in priority areas undoubtedly offers vast potential for new, challenging and exciting discoveries. This is more so with the introduction of a group of chemical called surfactant. In the industrial application the surfactants are used either as essential addictives or processing aids or in many cases as only a minor part of a particular system or formulation. Here the surfactant may be regarded as a “performance” or effect chemical, whereby small changes in molecular structure can result in dramatic changes in its phase behavior and performance.